Milkman - Burns, Anna, 1962- (London : Faber & Faber, 2018)
In Northern Ireland during the Troubles of the 1970s, an unnamed narrator finds herself targeted by a high-ranking dissident known as Milkman.
ENH, AAL
Book Finder International, R K Corporation
Man Booker Prize for Fiction, 2018.
Keywords: Sisters -- Fiction; Stalking -- Fiction; FICTION -- Literary; English fiction; Northern Ireland -- History -- 1968-1998 -- Fiction